The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.21608/edj.2018.78082
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Effect of Alcohol and Non-Alcohol Based Mouth Rinses on Color Stability of CAD/CAM Resin Ceramic and Feldspathic Ceramics

Abstract: Objectives:The aim of this study was to evaluate in vitro color stability of resin ceramic and feldspathic porcelain with two different mouth rinses: non-alcohol based 0.12% Chlorhexidine digluconate (CHX), and alcohol-based Listerine ® .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The result of present study revealed that chlorhexidine mouthwash increased staining ability of the three hybrid materials. This result agreed with a previous study 12 which showed that non-alcohol group of mouth rinses such as chlorhexidine significantly changed the color of two ceramics materials (Vita Enamic& Vitablocks Mark II).…”
Section: Discussionsupporting
confidence: 93%
“…The result of present study revealed that chlorhexidine mouthwash increased staining ability of the three hybrid materials. This result agreed with a previous study 12 which showed that non-alcohol group of mouth rinses such as chlorhexidine significantly changed the color of two ceramics materials (Vita Enamic& Vitablocks Mark II).…”
Section: Discussionsupporting
confidence: 93%
“…[20] So, this study examined the effect of Listerine mouth rinse on the surface roughness of three hybrid ceramic materials (Vita Enamic, Shofu HC, Nacera Hybrid) after immersion in 20 ml for 120 days at 37 C, replenishing every 12 hours which equals 2min daily mouth wash using for ten years. [14] The null hypothesis of this study was rejected as, the results of the current study showed increase in the Surface roughness measurements (Ra) value of the three hybrid materials in comparison to its base line values after immersion in mouth rinse, with the highest value in shofu HC then followed by Nacera Hybrid and Vita Enameic respectively.…”
Section: Discussionmentioning
confidence: 72%
“…Listerine mouth wash consists of Eucalyptol (0.092%), Thymol (0.064%), Methyl Salicylate (0.06%) and Menthol (0.042) antiplaque\ antigingivitis, relatively with low PH making it acidic to our neutral saliva level. [14] At the end of the days all specimens were taken out and washed with distilled water, dried, and subjected to the non-contact pro lometer to measure the surface roughness.…”
Section: Measuring Procedures With Pro Lometermentioning
confidence: 99%